Bureaucracy norms and market size - Arkadi Koziashvili; Shmuel Nitzan; Yossef Tobol (Institute for Advanced Studies (IHS), 2010)
This paper proposes a new model of market structure determination. It demonstrates that market structure need not be the result of ideology, political power, collusion among producers or the nature of the technology. In our setting, it is determined by bureaucrats who maximize their share of the industry profits. The approach is illustrated by studying the relationship between industry size and the existing institutional norm and by identifying the bureaucrats' most preferred norm. In the latter context, we establish the fundamental inverse relationship between the costs of interaction with government officials and industry size.
Keywords: D72; D73; 330; institutional norms; bureaucracy costs; norm viability; industry size; Normung; Folgekosten; Marktstruktur; Industriestruktur; Theorie